Oncostatin M promotes epithelial barrier dysfunction in patients with eosinophilic chronic rhinosinusitis with nasal polyps - Wang, Bao-Feng; Wang, Ying-Ying; Lin, Hai; Yi, Yun-Lan (Tissue barriers, 2024)
Oncostatin M (OSM) may be involved in the promotion of mucosal epithelial barrier dysfunction in patients with eosinophilic chronic rhinosinusitis with nasal polyps (Eos CRSwNP) by inducing matrix metalloproteinase (MMP) -1 and -7. The aim was to evaluate the roles and mechanisms of action of OSM on MMP-1 and -7 synthesis from nasal epithelial cells (NECs). OSM, OSM receptor (OSMR), MMP-1 and -7 expression was evaluated in nasal mucosa or primary NECs from scrapings by quantitative polymerase chain reaction (qPCR), immunofluorescence and immunohistochemistry. OSM and other cytokines were used to stimulate air-liquid interface (ALI) cultured NECs. qPCR, enzyme-linked immunosorbent assay (ELISA) and immunofluorescence were used to evaluate the expression of OSMR, MMP-1, -7 and occludin in NECs. Elevated levels of OSMRβ, MMP-1 and -7 were found in the tissues and scraped NECs of Eos CRSwNP in comparison to them obtained from the inferior turbinate (IT) and control subjects. The levels of OSM and OSMRβ mRNA in tissues were positively correlated with the levels of MMP-1 and -7. OSM stimulation of NECs increased the expression of MMP-1 and -7, and the responses were suppressed by a STAT3 inhibitor, and a PI3K inhibitor respectively. In parallel studies, we found that stimulation with OSM disrupted the localization of occludin, a tight junction protein in NECs. The response was suppressed by a pan-MMP inhibitor. OSM induces the synthesis and release of MMP-1 and -7 in NECs. Furthermore, MMP-1 and -7 promote mucosal epithelial barrier dysfunction in patients with Eos CRSwNP.